Patrimônio e imaginário: os construtores da Igreja de Santo Alexandre na Amazônia Colonial - MORAES, Maria Vitória Andrade (2024)
The church of Santo Alexandre was built in the 17th century in Santa Maria de Belém do Grão-Pará and is today one of the city's most important tourist attractions. The aim of this work is to investigate the relationship between the imaginary that the so-called “common sense” has about the Church of Santo Alexandre in the present day and about the indigenous, black and mestizo people who built this building, bearing in mind that these individuals have little visibility within history. It is therefore necessary to identify the 18th century individuals who took part in the construction of this place and to investigate their participation in the process of building the church. To do this, we analyzed the documentary source Catalogo deste Colégio de Santo Alexandre, seos bens, officinas, fazendas, servos, gados, dispendios e dividas activas e passivas in which we verified the identity of these workers and their trades. In addition, we contextualized the world of work in that period and analyzed the questionnaire given to the students in order to analyze how these subjects are perceived in the present. As a result, we observed that these workers are not perceived by the students and we will discuss the possible reasons.